A Hydrological-slope stability model for shallow landslide prediction in the Injisuthi Valley, KwaZulu-Natal Drakensberg - Meiklejohn, K.I. (Ian) (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2006.